Comparison of Hemodynamic Changes after Use of Intrathecal 0.75% Hyperbaric Bupivacaine Versus 0.5% Hyperbaric Bupivacaine with Dexmeditomidine in Patients Undergoing Cesarean Section - Muhammad Nadeem Khan, Hina Zubair, Noreen Rasul, Saima Parveen, Aurooj Fatima, Shahid Adalt (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare analysis of hemodynamic changes after use of intrathecal 0.75% and 0.5% hyperbaric bupivacaine with dexmedetomidine in cesarean section patients. Study Design: Comparative analytical study Place and Duration of Study: Divisional Headquarters Teaching Hospital Mirpur from 1st April 2020 to 30th April 2021. Methodology: Seventy women were enrolled as study participants. Full term pregnant women between the age of 20-35 years were enrolled. These women were further grouped into two major groups with both groups having equal number of participant (35 in each group). Group A consisted of those women who were given 12mg of 0.5% hyperbaric bupivacaine with 1µg dexmedetomidine while Group B women were intervened with 12mg 0.75% hyperbaric bupivacaine. The localized anesthesia with 2-3ml xylocaine (2%) was administered within intended space in all patients. A 25-gauge needle was used post confirmation of the free cerebrospinal fluid flow. Patient’s vital signs were continuously monitored. Results: The mean age was 31±4 years in group A while it was 27±4 year in group B. The post-operative parameters presented a decrease in blood pressure among both group women. The pulse rate showed that group A had slight higher reduction in pulse than group B however the difference was not significant (p=0.46).Both groups required ephedrine injections for substantial decrease in blood pressure. Conclusion: Patients administered with 0.75% hyperbaric bupivacaine for lower segment caesarean section showed significant and relevantly more hemodynamic alterations than 0.5% hyperbaric bupivacaine with Dexmedetomidine.